Ultra-Flattened Normal Dispersion Fiber for Supercontinuum and Dissipative Soliton Resonance Generation at 2 μm - Tianye Huang; Qian Wei; Zhichao Wu; Xu Wu; Pan Huang; Zhuo Cheng; Perry Ping Shum (IEEE Photonics Journal)
In this paper, we propose a photonic crystal fiber with broadband ultra-flattened normal dispersion at 2 μm. In this fiber, a subwavelength air hole in the core region and air holes arrangement in the cladding region are used to control the property of dispersion. With optimized design, the dispersion of the proposed ultra-flattened normal dispersion fiber (UNDF) can be kept within –72.4 to –73.15 ps·nm–1km–1 from 1750 to 2350 nm wavelength. Benefiting from this advantage, the fiber shows great potential in the applications of coherent supercontinuum (SC) generation and dissipative soliton resonance (DSR) generation in thulium-doped fiber lasers. According to our investigation, coherent SC with 10-dB bandwidth of 238 nm can be obtained by using 50-cm UNDF. Furthermore, by constructing a UNDF-based nonlinear optical loop mirror as a saturable absorber, we specifically investigate the field evolution from dissipative soliton to DSR in passively mode-locked lasers. The proposed UNDF can be a key component for various laser sources in a 2-μm band.